Moodle Cloud as the Developing Listening E-Learning Media in SMP Negeri 7 Medan - Nora Ronita Dewi; Juli Rachmadani Hasibuan; Masitowarni Siregar; Anggraini Thesisia Saragih; Dicki Darmawan (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2019)
The study was conducted to establish listening media for Grade VII of Junior High School Students. Research and Development (R&D) was conducted in the study. Listening media was designed through six stages namely. (1) Gathering information and data; (2) analyzing data; (3) designing materials; (4) validating by experts; (5) revising; and (6) final product. The data were collected by conducting interview to English teacher and distributing questionnaire to one class of grade VII consisting of 30 students to get the students’ needs in improving listening skill. The interview and questionnaire results showed that the students needed English Listening Media which could motivate and encourage the students to speak actively in English since both listening and speaking are integrated each other. The authority had assessed the media produced. The outcome of the research was an E-learning media named Moodle Cloud. The rate of assessment of the product was 93.55%. Therefore all the features were categorized as a relevant and effective media in improving students’ listening skill.